PENGETAHUAN, SIKAP, DAN PRAKTEK GIZI SERTA TINGKAT KONSUMSI IBU HAMIL DI KELURAHAN KERAMAT JATI DAN KELURAHAN RAGUNAN PROPINSI DKI JAKARTA - Nadiya Mawaddah; Hardinsyah Hardinsyah (Food and Nutrition Society of Indonesia, 2008)
The aim of this research is to understand the knowledge, attitude, and practice of nutrition and nutrient adequacy level (energy, protein, vitamin A, and Iron) of pregnant women. This research useda cross sectional study design. Research location implemented sprinkle programme. The sample was taken purposively with criteria not the first pregnancy, the age of pregnancy is between 8-28 weeks, and they are willing to be interviewed. The number of samples that were chosen are 100 pregnant women. Data that were collected were analyzed descriptively and statistically. In general, part (26%) of pregnant women had low nutrition knowledge. More than a half (71%) of pregnant women had moderate nutrition attitude. A half (50%) of pregnant women had good nutrition practice. Based on Spearman analysis, there were significant correlation between education level and nutrition knowledge (r=0.35, p<0.05), between nutrition knowledge and nutrition attitude (r=0.34, p<0.05), between nutrition knowledge and nutrition practice (r=0.266, p<0.05). This research showed adequacy level of protein and iron were inadequate. Adequacy level of energy, protein, vitamin A, and iron pregnant women in Kramat Jati was lower than Ragunan. Based on Spearman analysis there was no correlation between nutrition knowledge and consumption rate of energy, protein, and iron. While there is significant correlation between nutrition knowledge of pregnant women and consumption rate of vitamin A. Adequacy level of energy was affected by nutrition practice. Pregnant women with good nutrition practice had 16.7 times higher adequacy level of energy. Adequacy level of protein was affected by family size and nutrition practice. Income, family size, and nutrition practice didn’t affect the adequacy level of iron pregnant women. Adequacy level of vitamin A was affected by nutrition practice.